House Rental System For UMP Student - Muhammad Aslam, Mat Asri (2023)
UniHomes is a web-based solution that has been designed to provide an one stop center for the student to search for house or rooms to rent. The current problem that is faced by the student when they are searching for accommodations are time consuming as they need to go to different platforms, lack of transparency that can lead to scam and lastly there few landlords that are willing to rent their property to the students. To tackle these challenges, UniHomes is develop as a web-based system that utilize the current technology with a user friendly interface. This approach facilitates easy access for the landlords, students and PETAKOM easy to use the system even they have limited technical knowledge. As the system is develop as web based it make it easier to be access at any place at any time using any devices that support browsers. The UniHomes has been tested with a group of students and landlords and has received positive feedback with the User Acceptance Test result in as 10 out of 10 testers are satisfied. The system has improved the efficiency and transparency of property management. moreover, UniHomes has been designed to meet the specific needs of property managers and landlords, and as a result, it has been well received by those who have tested it. In conclusion, UniHomes is a valuable tool for students and landlords to streamline their property management process and improve the efficiency and transparency of their operations. The system h has the potential to revolutionize the way rental properties are managed. UniHomes is seen to become the go-to solution for students and landlords who want to improve the way they manage their rental properties.